The peroxisomal Lon protease LonP2 in aging and disease: functions and comparisons with mitochondrial Lon protease LonP1. (8th February 2016) - Pomatto, Laura C. D.; Raynes, Rachel; Davies, Kelvin J. A.
ABSTRACT: Peroxisomes are ubiquitous eukaryotic organelles with the primary role of breaking down very long‐ and branched‐chain fatty acids for subsequent β‐oxidation in the mitochondrion. Like mitochondria, peroxisomes are major sites for oxygen utilization and potential contributors to cellular oxidative stress. The accumulation of oxidatively damaged proteins, which often develop into inclusion bodies (of oxidized, aggregated, and cross‐linked proteins) within both mitochondria and peroxisomes, results in loss of organelle function that may contribute to the aging process. Both organelles possess an isoform of the Lon protease that is responsible for degrading proteins damaged by oxidation. While the importance of mitochondrial Lon (LonP1) in relation to oxidative stress and aging has been established, little is known regarding the role of LonP2 and aging‐related changes in the peroxisome. Recently, peroxisome dysfunction has been associated with aging‐related diseases indicating that peroxisome maintenance is a critical component of 'healthy aging'. Although mitochondria and peroxisomes are both needed for fatty acid metabolism, little work has focused on understanding the relationship between these two organelles including how age‐dependent changes in one organelle may be detrimental for the other. Herein, we summarize findings that establish proteolytic degradation of damaged proteins by the Lon protease as a vital mechanism to maintain protein homeostasis within the peroxisome. Due to the metabolic coordination between peroxisomes and mitochondria, understanding the role of Lon in the aging peroxisome may help to elucidate cellular causes for both peroxisome and mitochondrial dysfunction.